BONEKA “MENONG” SEBAGAI IKON PURWAKARTA: PENGARUH MASYARAKAT TERHADAP WUJUD KERAMIK “MENONG” - Futty, Andini; Cahyana, Agus; Falah, Asep Miftahul (Jurusan Seni Rupa ISBI Bandung, 2021)
The research in this paper aims to describe how the development, process of creation, anthropological concepts, and the influence of society on the form of